The logic behind the resurgence of microbreweries in Brussels - Pauline Delperdange (Brussels Studies, 2021)
Microbreweries are an emblematic example of the renewed growth in artisanal activities and are undergoing a significant resurgence in Brussels. Our article discusses the return of these productive activities to the city, answering these questions: by whom, how and where is beer produced in Brussels? First, we identify the dynamics of the location of past and present activities in the urban area and the economic hinterland of the region. Then, based on the analysis of interviews conducted with fifteen or so brewers, we discuss the heterogeneity of the Brussels microbrewery world, through the identification of multiple entrepreneurial approaches which imply a wide range of conceptions of urban production and the relationship to space.